Legal education in crisis and construction of new post-pandemic paradigms - Durlo, Juliana Vendramini; Gentil, Plínio A. B. (Seven Editora, 2023)
This article addresses topics related to the future of legal education in Brazilian universities in the post-pandemic of the so-called new coronavirus. As a specific objective, it intends to expose the change that occurred in the need for online undergraduate courses, in addition to reflecting on the economic gain and educational loss of this system. To materialize this research, the methodology used in the elaboration of the article is a qualitative analysis via bibliographic review, carried out through exploration through the survey of scientific articles indexed in appropriate databases such as Scielo, Google Scholar, and in the public domain. In this way, the bibliographic research consisted of reading texts related to the subject, prioritizing the fundamental bibliography. The problem to be researched starts from the premise that legal education in Brazil deserves a new educational perspective, and that means, in addition to the method, support in critical and interdisciplinary law. The relevance of the work takes place amid the new coronavirus pandemic, which transformed, overnight, access to education and its practice. It also seeks to initiate a reflection on the training of uncritical professionals, mere repeaters of given knowledge.  Considering the expression "theoretical common sense", it is expected to contribute to a critical look at legal science and its teaching model amid profound social change. DOI:https://doi.org/10.56238/alookdevelopv1-034